High-Intensity Interval Training as an Efficacious Alternative to Moderate-Intensity Continuous Training for Adults with Prediabetes - Mary E. Jung; Jessica E. Bourne; Mark R. Beauchamp; Emily Robinson; Jonathan P. Little (Journal of Diabetes Research)
Aims. High-intensity interval training (HIIT) leads to improvements in various markers of cardiometabolic health but adherence to HIIT following a supervised laboratory intervention has yet to be tested. We compared self-report and objective measures of physical activity after one month of independent exercise in individuals with prediabetes who were randomized to HIIT (n=15) or traditional moderate-intensity continuous training (MICT, n=17). Method. After completing 10 sessions of supervised training participants were asked to perform HIIT or MICT three times per week for four weeks. Results. Individuals in HIIT (89 ± 11%) adhered to their prescribed protocol to a greater extent than individuals in MICT (71 ± 31%) as determined by training logs completed over one-month follow-up (P = 0.05, Cohen’s d = 0.75). Minutes spent in vigorous physical activity per week measured by accelerometer were higher in HIIT (24 ± 18) as compared to MICT (11 ± 10) at one-month follow-up (P = 0.049, Cohen’s d = 0.92). Cardiorespiratory fitness and systolic blood pressure assessed at one-month follow-up were equally improved (P’s < 0.05). Conclusions. This study provides preliminary evidence that individuals with prediabetes can adhere to HIIT over the short-term and do so at a level that is greater than MICT.